SONOICE! a Sonar–Voice dynamic user interface for assisting individuals with blindness and visual impairment in pinpointing elements in 2D tactile readers - Ramôa, Gaspar; Schmidt, Vincent; Schwarz, Thorsten; Stiefelhagen, Rainer; König, Peter (Frontiers in Rehabilitation Sciences, 2024)
Pinpointing elements on large tactile surfaces is challenging for individuals with blindness and visual impairment (BVI) seeking to access two-dimensional (2D) information. This is particularly evident when using 2D tactile readers, devices designed to provide 2D information using static tactile representations with audio explanations. Traditional pinpointing methods, such as sighted assistance and trial-and-error, are limited and inefficient, while alternative pinpointing user interfaces (UI) are still emerging and need advancement. To address these limitations, we develop three distinct navigation UIs using a user-centred design approach: Sonar (proximity-radar sonification), Voice (direct clock-system speech instructions), and Sonoice, a new method that combines elements of both. The navigation UIs were incorporated into the Tactonom Reader device to conduct a trial study with ten BVI participants. Our UIs exhibited superior performance and higher user satisfaction than the conventional trial-and-error approach, showcasing scalability to varied assistive technology and their effectiveness regardless of graphic complexity. The innovative Sonoice approach achieved the highest efficiency in pinpointing elements, but user satisfaction was highest with the Sonar approach. Surprisingly, participant preferences varied and did not always align with their most effective strategy, underscoring the importance of accommodating individual user preferences and contextual factors when choosing between the three UIs. While more extensive training may reveal further differences between these UIs, our results emphasise the significance of offering diverse options to meet user needs. Altogether, the results provide valuable insights for improving the functionality of 2D tactile readers, thereby contributing to the future development of accessible technology.